Biofertilizantes foliares y variedades en el rendimiento de Coriandrum sativum. culantro. Zungarococha, Loreto, 2023 - Pardo Arancibia, Jose (2024)
Culantro cultivation is a traditional food and is used in many Amazonian foods as an aromatizer and flavoring agent. It is necessary to know the variety that is most accepted and the use of biofertilizer as a complement to the nutrition of this plant. For this reason, this study was made. research work: "FOLIAR BIOFERTILIZERS AND VARIETIES IN THE YIELD OF Coriandrum sativum. CULANTRO. ZUNGAROCOCHA, LORETO, 2023". The evaluations were carried out 60 days after sowing, the experimental units have an area of 3.0 m2. With a Complete Random Block Design with four treatments and four repetitions, the treatments under study were: T1 (C1B1), T2 (C1B2), T3 (C2B1), and T4 (C2B2), where C1= Green center, C2= purple stem cilantro, B1= humus leachate, B2= Biol, the best treatment was T1 (C1= Green Coentro B1= humus leachate), with the following results in plant height with 26.18 centimeters, plant weight/bundle lines with 277.9 grams, in root length with 14.9 centimeters, number of plants/bundle with 926.34 plants, in terms of root weight/10 plants with 3.25 grams and in the weight of cilantro/6000m2 with 8 337.0 kilos.